THE INHIBITION OF CALCITE DISSOLUTION PRECIPITATION - 1,2-DICARBOXYLIC ACIDS - Compton, R; Brown, C (1995)
The dissolution of calcite under conditions of high pH (8.0-9.0) is shown to be strongly inhibited by ca. 10 mM levels of the fully deprotonated forms of succinic acid, phthalic acid, and maleic acid. Channel flow cell measurements are used in each case to deduce the appropriate rate law for dissolution. For the maleate dianion it is demonstrated that the inhibition is likely due to the blocking of dissolution/growth sites at which CaCO3 units are incorporated into or removed from the crystal lattice, whereas for the other two ions it arises from competitive Langmuirian adsorption of the dicarboxylate ions and CO3 2- on the calcite surface.